Pathogenesis of Congenital Malformations: Possible Role of Oxidative Stress - Impellizzeri, Pietro; Nascimben, Francesca; Di Fabrizio, Donatella; Antonuccio, Pietro; Antonelli, Enrica; Peri, Flora Maria; Calabrese, Ugo; Arena, Salvatore; Romeo, Carmelo (American Journal of Perinatology, 2020)
Objective Congenital anomalies are important causes of morbidity and mortality in children. Oxidative stress (OS) is involved in the physiopathology of pregnancy-related congenital malformations. This review summarizes the role of OS in the pathogenesis of congenital malformations; in particular, its purpose is to describe how OS influences the development of heart congenital malformations, oesophageal atresia, biliary atresia, diaphragmatic hernia, and autosomal dominant polycystic kidney disease.Study Design Systematic review of previous studies about the role of OS in pregnancy and its possible effects in developing of congenital malformations. One electronic database (PubMed) was searched and reference lists were checked.Results An imbalance between the production of reactive oxygen species (ROS) and antioxidant defense can occur early in pregnancy and continue in the postnatal life, producing OS. It may destroy the signaling pathways needed for a correct embryogenesis leading to birth defects. In fact, cell functions, especially during embryogenesis, needs specific signaling pathways to regulate the development. These pathways are sensitive to both endogenous and exogenous factors; therefore, they can produce structural alterations of the developing fetus.Conclusion Because OS plays a significant role in pathogenesis of congenital malformations, studies should be developed in order to better define their OS mechanisms and the beneficial effects of supplemental therapeutic strategies.Key Points
Keywords: oxidative stress; newborns; congenital malformations; therapeutic strategies